Understanding Sharia Compliance According To Indonesian Muslim Entrepreneurs And Business People - Ika Yunia Fauzia; Wiwik Lestari; Tatik Suryani (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2020)
This research aims at understanding the concept of Sharia compliance, according to Muslim business people and entrepreneurs. These people, over the years, believe that their business is in full conformity with Sharia. Using a qualitative approach coupled with an ethnographic analysis, this research finds that their business is in line with Sharia in terms of its meanings, forms, functions, benefits and values. This study also finds that there are similarities between one respondent to others with regard to the underlying meaning of Shariah compliance. However, they have different understanding concerning the meaning of usury and interest in conventional banking.Penelitian ini bertujuan melihat pemaknaan kesesuaian dengan syariah (shariah compliance) menurut para pebisnis dan wirausahawan Muslim. Kelompok ini, selama bertahun-tahun, meyakini bahwa usaha yang mereka jalankan sudah sesuai dengan syariah. Penelitian ini menggunakan pendekatan kualitatif dengan studi etnografi. Selanjutnya, penelitian ini menemukan bahwa para bisnis yang dijalankan oleh responden berkesesuaian dengan syariah dalam hal makna, bentuk, fungsi, manfaat, dan nilai. Ditemukan juga bahwa ada kesamaan pemahaman antara satu responden dengan yang lain terkait dengan pemaknaan shariah compliance. Meskipun demikian, ada perbedaan dalam memahami hukum tentang riba dan bunga pada bank konvensional.